AnalisisRegresi Binomial Negatif untuk Pemodelan Angka Positif Penyakit Kusta di Jawa Timur - Dhahari, Nadiya Mushma; Sofro, A'yunin (MATHunesa: Jurnal Ilmiah Matematika, 2023)
Leprosy is a chronic disease caused by Mycobacterium leprae, which injures the peripheral nerves (sensory, motor and autonomic functions). Delayed treatment can result in permanent damage to the eyes, hands and feet. The purpose of this research is to identify the factors that influence the positive rate of leprosy in East Java. Factors that can influence include population density, the number of villages or sub-districts with health facilities, the percentage of people with health complaints, the percentage of households with adequate sanitation facilities, the percentage of poor people, the number of health workers, and the percentage who have health insurance. amount. Percentage of workers and those with health insurance. The method used is negative binomial regression method. This is one of the methods used to overcome data overdispersion in Poisson regression. The data for this study used data obtained from the Central Bureau of Statistics and Publication of the East Java Health Service in 2021. The results showed that population density, the percentage of people with health complaints, and the percentage of poor people were factors that influenced the significance of leprosy sufferers in East Java in 2021. Keywords: leprosy, Poisson regression, overdispersion, negative binomial regression.